Decentralising and Democratising Energy with Neel Tamhane, Solar Strategy Lead from SPACE10 - Maria Tzika (Urban Transcripts, 2021)
I first came across Neel Tamhane’s work when he was featured in the documentary 2040. He was working in Bangladesh, revolutionising the distribution of solar power and helping villages to produce, consume and share or sell electricity. This democratic approach to energy production gave a new lifeline to people and communities that were under-resourced and living in poverty. I found his approach extremely inspiring and an eye opener. A transition to renewable energies should also be a transition to a localised and self organised economy. Neel is now working at SPACE10, developing energy products and services like SOLshare, a localised energy trading platform. We are very happy to have him here and help spread the message of his work.